Makna “Pacaran Syar’i” pada Film Cinta Subuh - Lovina Fernando, Giska; Akhmad Rifa'i (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Many discourses in social life are found, one of which is the discourse of "syar'i dating". The word "pacaran syari" has become an increasingly interesting topic of conversation in the context of modern Indonesian pop culture, especially for films in Indonesia, one of which is the religious film "Cinta Subuh". This study aims to determine the meaning of "syar'i courtship" shown in the film "Cinta Subuh," which focuses on how this discourse is portrayed in narrative, characters, and dialogue. This type of research is qualitative research, through Teun Van Dijk's critical discourse analysis approach. The findings of this study provide an understanding that the meaning of "sharia dating" in films affects viewers' perceptions of romantic relationships. The study also found that narrative, characters, and dialogue exist in the meaning of "syar'i courtship". This research is expected to contribute in understanding how film becomes a medium in designing, reflecting, and influencing people's views on other terms or meanings in the context of modern Indonesian pop culture.